Kinematic analysis of five ankle inversion ligamentous sprain injury cases in tennis - Fong, D. T. P. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Ankle sprain injury is very common in sport and this study investigated its kinematics. Five injury incidents captured in televised tennis competitions were analysed by a modelbased image-matching motion analysis technique. Results showed a trend of sudden ankle inversion and internal rotation but not plantarflexion. The peak inversion was achieved explosively in a very short time, which is within 0.09-0.17s, after the foot strike. All but one case presented with a slightly inverted ankle joint at foot strike of 10-24 degrees, which should have incited the injury event. We recommend tennis players who perform repetitive sideward cutting motions to attempt to land with a neutral ankle orientation, and to keep their centre of plantar pressure from shifting to the lateral aspect, in order to prevent an ankle inversion sprain injury.